Augmented Reality in Improving Writing Skills Learning Experiences in Vocational High School Students - Sari, Ni Wayan Ayu Permata; Sudrajat, Yayan; Casande, Suwito; Syarif, Muhammad; Monarchi, Angie Melody (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
This arises from adapting 21st century learning in the form of learning skills, literacy skills, life skills, skills and attitudes, as well as mastery of technology. 21st century learning will improve students' learning experience, especially learning Indonesian with the topic of writing internship reports even though the teacher still provides stimulants in class using learning media. Augmented Reality (AR). The purpose of this research is for media development Augmented Reality (AR) in improving the learning experience of writing skills, knowing the suitability of the media Augmented Reality (AR) in improving the experience of learning writing skills, and knowing the effectiveness of the media Augmented Reality (AR) in improving the experience of learning writing skills Research methods used is research and development or Research and Development (R&D) which adopts the Lee and Owen development model with 5 stages, namely needs analysis, analysis front-end, design, development, implementation, and evaluation (ADDIE). The results of the development are application products with learning media augmented reality.